The Effects of Organizational Culture on Employee Performance: A Study of the Edge Newspaper - Sundararajan, Thanushrii P.K.; Kee, Daisy Mui Hung; Albert, Paul Jason; Subramaniam, Maniratnam; Thirupathi, Harichandran; Angarita, Laura Sofia Cuellar; Restrepo, Camilo PÃ©rez; Lopez, Carolina Ardila; Vashney, Kushal; Kumar, Kalyani Prem; Pandey, Rudresh (International Journal of Applied Business and International Management, 2020)
This research aims to examine the effect of organizational culture on employee performance. The research was conducted by interviewing the Edge Newspaper Sdn Bhd Companyâ€™s top management and their employees. Apart from that, data collection will be based on observations from surveys and journals. These collected data were used to test our hypothesis that is â€˜A good employee behaviour will increase business productivity, lower absenteeism, and achieve turnoverâ€. It is proven that a positive relationship exists between organizational culture and employee behaviour. These findings provide new insights for the management of the effects of organizational culture on its employee performances. In addition, this research enhances the understanding of employee behaviour, possibly utilized by top management to encourage and manage their employees.